Clinical Characteristics and Microbiological Profile of Oral Candidiasis among HIV-Positive Patients in Indonesia: A Literature Review - Prameshvari, Putu Lovina Indra; Permana, Putu Bagus Dharma; Hidayati, Afif Nurul; Murtiastutik, Dwi; Arfijanto, Muhammad Vitanata (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2025)
Background: As the country with the highest identified active cases of HIV/AIDS across Southeast Asia, Indonesia faces a massive challenge in providing adequate antiretroviral therapy (ART) coverage to prevent disease progression and mortality.  Oral candidiasis (OC) is the most frequently identified oral manifestation of HIV infection and represents the degree of immunosuppression, treatment failure, and prognosis among people living with HIV/AIDS. Demographic characteristics, clinical types, and causative pathogens of OC vary between different geographical and socioeconomic settings. Hence, the role of oral candidiasis is crucial in developing effective strategies to address the HIV-related burden in Indonesia. Review: This literature review evaluated 11 descriptive studies conducted across eight major cities in Indonesia, comprising 764 HIV-positive patients diagnosed with OC. Most affected individuals were male and exhibited advanced immunosuppression, with the majority presenting CD4+ counts below 200 cells/mm³. Six clinical variants of OC were identified, with pseudomembranous candidiasis being the predominant form, followed by angular cheilitis, erythematous candidiasis, hyperplastic candidiasis, and sporadic cases of atrophic candidiasis and denture stomatitis. Microbiological findings showed Candida albicans as the leading etiologic species; however, non-albicans Candida (NAC)—particularly C. krusei, C. glabrata, and C. tropicalis—demonstrated notable prevalence, including mixed colonization with C. albicans. The rise of NAC species highlights concerns regarding antifungal resistance in the ART era. Conclusion: Oral candidiasis serves as an important clinical finding among patients living with HIV/AIDS, and its appropriate management is necessary not only to prevent further complications but also to mitigate the recent development of antifungal resistance.